ANALISIS INTEGRASI PASAR LADA DI PROVINSI LAMPUNG DENGAN PASAR INTERNASIONAL - Novi Rosanti; Rofi Al Akbar; Wan Abbas Zakaria (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
Pepper is one of the plantation commodities traded in the international market. The price of pepper at the producer level is determined by the market price of pepper on the world market. This research aims to analyze the market integration between the Lampung Province pepper market and the international market. This study uses secondary data in the form of monthly pepper prices at the producer level of Lampung Province, the domestic market of Lampung Province and the international market for the period January 2013 - December 2020. The data analysis uses the Vector Error Correction Model (VECM). The results showed that there was integration between the pepper market at the producer level of Lampung Province, the domestic market of Lampung Province and the international market in the long and short term, but the price changes that occurred could not be conveyed perfectly between markets due to the adjustment time in each market in response. price changes that occur.